Increased Surgeon-specific Experience and Volume is Correlated With Improved Clinical Outcomes in Lumbar Fusion Patients. Issue 2 (25th March 2023) - Hines, Kevin; Philipp, Lucas; Thalheimer, Sara; Montenegro, Thiago S.; Gonzalez, Glenn A.; Hughes, Liam P.; Leibold, Adam; Mahtabfar, Aria; Franco, Daniel; Heller, Joshua E.; Jallo, Jack; Prasad, Srinivas; et al.
Abstract : Study Design: The present study design was that of a single center, retrospective cohort study to evaluate the influence of surgeon-specific factors on patient functional outcomes at 6 months following lumbar fusion. Retrospective review of a prospectively maintained database of patients who underwent neurosurgical lumbar instrumented arthrodesis identified the present study population. Objective: This study seeks to evaluate surgeon-specific variable effects on patient-reported outcomes such as Oswestry Disability Index (ODI) and the effect of North American Spine Society (NASS) concordance on outcomes in the setting of variable surgeon characteristics. Summary of Background Data: Lumbar fusion is one of the fastest growing procedures performed in the United States. Although the impact of surgeon-specific factors on patient-reported outcomes has been contested, studies examining these effects are limited. Methods: This is a single center, retrospective cohort study analyzing a prospectively maintained database of patients who underwent neurosurgical lumbar instrumented arthrodesis by 1 of 5 neurosurgery fellowship trained spine surgeons. The primary outcome was improvement of ODI at 6 months postoperative follow-up compared with preoperative ODI. Results: A total of 307 patients were identified for analysis. Overall, 62% of the study population achieved minimum clinically important difference (MCID) in ODI score at 6 months. Years in practice and volume of lumbar fusions were statistically significant independent predictors of MCID ODI on multivariable logistic regression ( P =0.0340 and P =0.0343, respectively). Concordance with evidence-based criteria conferred a 3.16 (95% CI: 1.03, 9.65) times greater odds of achieving MCID. Conclusion: This study demonstrates that traditional surgeon-specific variables predicting surgical morbidity such as experience and procedural volume are also predictors of achieving MCID 6 months postoperatively from lumbar fusion. Independent of surgeon factors, however, adhering to evidence-based guidelines can lead to improved outcomes.